2012
DOI: 10.1111/j.1365-2591.2011.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of DNA damage and caspase activation in cytotoxicity and genotoxicity of macrophages induced by bisphenol‐A‐glycidyldimethacrylate

Abstract: Cytotoxicity and genotoxicity induced by BisGMA are mediated by DNA damage and caspase activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 31 publications
(58 reference statements)
8
51
0
1
Order By: Relevance
“…In this study, we also ascertained that the cell death patterns provoked by 0.5 mM Bis-GMA in HOK cells were mainly apoptosis. Our findings are in line with those of Chang et al (2010b) and Li et al (2012) in human dental pulp cells and murine macrophage cell line RAW264.7. However, Reichl et al (2006) have presented that Bis-GMA-induced mainly necrotic cell death in human gingival fibroblast (HGF), while apoptotic cell death events were very few.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we also ascertained that the cell death patterns provoked by 0.5 mM Bis-GMA in HOK cells were mainly apoptosis. Our findings are in line with those of Chang et al (2010b) and Li et al (2012) in human dental pulp cells and murine macrophage cell line RAW264.7. However, Reichl et al (2006) have presented that Bis-GMA-induced mainly necrotic cell death in human gingival fibroblast (HGF), while apoptotic cell death events were very few.…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, other researchers revealed that the mode of cell death due to BPA changed from apoptosis to necrosis and this was also associated with caspase activation (Li et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Pro-inflammatory cytokines and chemokines, including IL-1b, IL-6, TNF and monocyte chemoattractant protein-1 (MCP-1), are produced from hepatic macrophages in various murine models of liver injury (Tuñ on et al 2009;Zimmermann et al 2012;Shen et al 2015;Ferreira et al 2016). Furthermore, the release of these cytokines can activate macrophages during infection, injury and inflammation (Kim et al 2007;Li et al 2012). IL-1b also stimulates the production of other cytokines and recruits inflammatory cells (Tilg & Diehl 2000).…”
Section: Inflammatory Markersmentioning
confidence: 99%